For nature/with nature : new sustainable design scenarios / Claudio Gambardella, editor. - Gambardella, Claudio (Springer series in design and innovation, 2024)
This volume contributes to the construction of a multi-voice mosaic on the theme of nature and the relationship between man (understood as designer) and nature by emphasizing the innovative and sustainable proposals coming from the discipline of design, in its many facets and interdisciplinary contributions.